Membumikan tradisi riyadlah khataman Al-Qur’an di kalangan santri tahfidz putra YPP Al-Mardliyyah, Mojosari, Nganjuk - Binashrilah, Ahmad Fatih Alfaiz; Hakim, M. Abdul; Ayuningtiyas, Santi (KHIDMAH : Jurnal Pengabdian Masyarakat, 2025)
This research aims to establish the riyādlah khataman Al-Quran in the male tahfidz students of YPP Al-Mardliyyah PP. Mojosari, Nganjuk. The method used in this research is a qualitative method based on observation and interviews with related parties. The results obtained from the responses of the perpetrators of khataman activities are then combined with religious texts to support the validity of the results obtained. It can be concluded from this research that the tradition of khataman Al-Quran has a significant impact in facilitating the memorisation of Al-Quran, increasing the spirit of memorising Al-Quran, fostering self-confidence and promoting a sense of brotherhood among tahfidz Al-Quran students. This research contributes to the development of the tahfidz curriculum in YPP Al-Mardliyyah male dormitory as well as other tahfidz Al-Quran institutions